Hubungan antara Minat Belajar dan Kemampuan Berpikir Spasial Peserta Didik dengan Hasil Belajar Geografi di SMA Negeri 2 Pariaman - Fadila, Fadila; Nova, Sari (Lembaga Yasin AlSys, 2024)
The research aims to determine: 1. The relationship between learning interest and geography learning outcomes at SMA Negeri 2 Pariaman, 2. The relationship between spatial thinking ability and geography learning outcomes at SMA Negeri 2 Pariaman, and 3. The relationship between learning interest and spatial thinking ability with geography learning outcomes at SMA Negeri 2 Kota Pariaman. The research uses a quantitative correlational approach. The population and sample of the study consist of 141 students of class X.E, selected using a saturated sampling technique. The data collection methods include questionnaires, tests, and documentation. The data analysis techniques include instrument testing, descriptive statistical analysis, and hypothesis testing. The conclusions of the study are as follows: 1) There is a relationship between learning interest and learning outcomes, with a score of 10.2 and a correlation coefficient of 0.319, indicating a weak relationship. Good interest stimulates students' enthusiasm for learning. For example, geography material can stimulate students' interest in learning geography in class if it is presented in a relevant, engaging, and interactive manner. 2) There is a relationship between spatial thinking skills and learning outcomes, with a score of 10.7 and a correlation coefficient of 0.327, indicating a weak relationship. The discussion of the geosphere material as part of the spatial reasoning test includes understanding and analyzing various components and spatial relationships of the geosphere. 3) There is a correlation between learning interest and spatial thinking ability, with a learning score of 19.4 and a correlation coefficient of 0.440, indicating a moderate relationship. The research results show that factors such as learning interest and spatial thinking ability can contribute positively to learning outcomes. As learning interest and spatial thinking improve, learning outcomes tend to increase as well.